2020
DOI: 10.1063/1.5130452
|View full text |Cite
|
Sign up to set email alerts
|

Highly (001) oriented MnAl thin film fabricated on CoGa buffer layer

Abstract: 5 nm- and 15 nm-thick (001) oriented MnAl films were fabricated on CoGa buffer layers with various thermal treatments. The insertion of the CoGa layer was effective to obtain the square out-of-plane hysteresis loop even in the MnAl thickness of 5 nm. Highly (001) oriented MnAl film was obtained by depositing Mn and Al on CoGa at a substrate temperature of 200°C followed by annealing at 500°C. The perpendicular magnetic anisotropy was estimated to be 7.4±0.2 and 8.5±0.4 Merg/cc for 5 nm- and 15 nm-thick MnAl, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In order to fabricate smaller bit patterns than 80 nm, it is necessary to decrease the thickness of MnGa layer, because sharper transition interface between magnetic and non-magnetic areas will be realized by shortening the penetration depth of ion irradiation and suppressing ion scattering in MnGa layer. However, the Ms and the squareness of both MnAl and MnGa decrease with decreasing layer thickness from 15 nm to 5 nm 34) . Since it had been reported that the insertion of CoGa buffer Fig.…”
Section: L10 Mnal and Mnga Films Grown On Mgo (001)mentioning
confidence: 89%
See 2 more Smart Citations
“…In order to fabricate smaller bit patterns than 80 nm, it is necessary to decrease the thickness of MnGa layer, because sharper transition interface between magnetic and non-magnetic areas will be realized by shortening the penetration depth of ion irradiation and suppressing ion scattering in MnGa layer. However, the Ms and the squareness of both MnAl and MnGa decrease with decreasing layer thickness from 15 nm to 5 nm 34) . Since it had been reported that the insertion of CoGa buffer Fig.…”
Section: L10 Mnal and Mnga Films Grown On Mgo (001)mentioning
confidence: 89%
“…layer was effective to improve the degradation of Ms and squareness 35), 36) , Cr(2cnm)/MnAl(5cnm)/CoGa(0 or 30cnm) /Cr(20cnm)/MgO(001) films were fabricated by sputtering, where the CoGa/Cr layers were annealed at 600˚C after deposition at 400˚C and the MnAl layer was deposited at 200˚C. Figure 12 shows XRD profiles of 5nm thick MnAl films on Cr or CoGa buffer layer, where one of MnAl film on CoGa layer was post-annealed at Ta=500˚C and another was not annealed 34) . The 001 and 002 peaks from L10 MnAl were clearly observed in all films and both the insertion of the CoGa buffer layer and the post-annealing of the MnAl layer are effective to enhance 001 peak due to the ordered phase.…”
Section: A D V a N C E P U B L I C A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, relatively low temperature growth on a specific alloy template would be effective, as well known in tetragonal Mn-based Heusler alloys and those derivatives, for example. [34][35][36][37][38][39][40][41] Thus, it would be crucial to find good templates for obtaining the Heusler phase of NiCrMnSi, which is left as a future subject.…”
Section: Discussionmentioning
confidence: 99%
“…Such a current-induced spin-orbit torque switching of the magnetization is of importance when utilizing perpendicularly magnetized magnetic tunnel junctions, which have been suggested for magnetic random access memory usage. Further, CoGa was used as buffer layer to grow high quality MnAl(001) films [6]. Lau et al reported a high spin Hall effect in paramagnetic CoGa thin films [7,8].…”
Section: Introductionmentioning
confidence: 99%